INTERNALISASI NILAI ISLAM DALAM MEMBANGUN KEMANDIRIAN SOSIAL MELALUI FILANTROPI ISLAM BERBASIS ORGANISASI KEAGAMAAN DI PONOROGO - Katni, Katni; Rois, Adib Kusnul; Candrakusuma, Muslih; Iman, Nurul (MUADDIB Jurnal Kependidikan dan Keislaman, 2021)
This article discusses how Islamic religious organizations located in rural areas internalize Islamic values and carry out social programs by revitalizing Islamic philanthropic schemes. By taking the case in a village in the Ponorogo Regency, East Java, where two religious organizations Islamic Muhammadiyah and Nahdlatul Ulama fastabiqul Khairat through Islamic philanthropy programs in building social independence. This article states that the ability of the two Islamic religious organizations to involve local leaders and communities where the religious organizations are involved in socio-religious activities is one of the reasons why these two organizations are still able to survive until now. These two Islamic religious organizations are trying through various efforts as if they are in a contest to build social independence to understand, explore and practice Islamic values, which have increased from year to year. This article formulates in a context such as whether Islamic religious organizations in rural areas can transform values, transact values and "transinternalize Islamic values through Islamic philanthropy in building "social" independence.